Green Chemistry Education for Sustainable Development Goals (SDGs): A Systematic Literature Review - Dewiyanti Fadly; Vika Puji Cahyani (Jurusan Kimia FMIPA UNM, 2026)
Global environmental crises such as climate change, biodiversity loss, and chemical pollution demand scientific approaches that support sustainable development. One approach that has received widespread attention is green chemistry, which seeks to design safer, more efficient, and environmentally friendly chemical products and processes. This study aims to analyze the development of research on the relationship between green chemistry and the Sustainable Development Goals (SDGs) through a systematic bibliometric literature review. The research method refers to the PRISMA framework by searching and selecting scientific articles published in English over the past ten years. Publication data were then analyzed to identify research trends, key themes, and relationships between study topics. The analysis shows that research on green chemistry and the SDGs has increased significantly in recent years, indicating growing academic attention to the role of chemistry in supporting sustainable development. Existing studies generally highlight the contribution of green chemistry to waste reduction, energy efficiency, safer chemical use, and the development of environmentally friendly technologies. However, research gaps remain, particularly regarding a more systematic mapping of green chemistry principles with specific SDG indicators. Therefore, further research needs to develop an analytical approach that is able to measure the contribution of green chemistry to achieving SDG targets in a more integrated and indicator-based manner.